SIMOMI : Online Guidance and Consultation Based Mobile Application as Independent Learning Media on Lactation - Thathit Manon Andini (Universitas Muhammadiyah Malang, 2019)
Lactation management is an effort to support lactation success starting from pregnancy, childbirth, and breastfeeding. Parents learn about lactation management directly from counseling or independently from articles and books. Website and social media become favorite learning media because both media can be accessed anytime and anywhere. Considering the large number of smart phone users and the limited internet connection in Indonesia, we developed a mobile based lactation management application named SIMOMI. The development of SIMOMI application aims to enable the community (parents, prospective parents, and everyone who needs understanding of lactation) to learn independently about lactation whenever and wherever, whether offline or online. The method used in this research is design system. Features available on Simomi applications include online calculators, articles, and consultations. The product have been tested using black box method and User Experience Test by involving experts to know the readiness and response to the technology before publishing for general audience. The test results concluded that Simomi application has been able to run as the goal and the initial design especially on the features of the calculator. Through this SIMOMI application, the wider community especially LP3A which is concerned with the growth of children and the role of women, can be more active in supporting the government program, especially in the awareness movement of exclusive breastfeeding for the community. It is expected to support the fulfillment of nutrition and development of the baby to the maximum.